Preferensi Pakan Serangga Kumbang Daun (Epilachna varivestis) Dan Oteng-Oteng (Aulacophora similis) Dari Beberapa Jenis Tanaman Solanceae - Faizah Qonita Zhafirah; Nadila Margaretha; Herlin Arlika; Okta Dea Riani; Anggun Wicaksono (Jurnal Biologi dan Pembelajarannya (JB&P), 2024)
Insects are vertebrate animals classified in the phylum Arthropoda. Insects are one of the animals that are very numerous, one of which is in the insecta class, so the presence of insects really affects the ecosystem. This research aims to determine the food preferences of leaf beetles (Epilachna varivestis) and oteng- oteng (Aulacophora similis) from several types of Solanceae plants. The samples used in this research were the leaf beetle Epilachna varivestis and oteng-oteng (Aulacophora similis) and 5 types of Solanaceae plant leaves including cayenne pepper leaves, bird chili leaves, eggplant leaves, ciplukan leaves and takokak leaves. This observation was carried out to find out 1). How long does it take for the beetle to find its food? 2). Which type of leaf is eaten first and which type of leaf is eaten the most? 3). How long does it take for a beetle to eat this type of food? 4). Is there a switching of the beetle's eating pattern? Based on the results of observations made, the leaf beetle Epilachna sp apparently preferred cayenne pepper leaves (Capsicum frutescens) for 30 minutes slowly and stopped by the other four leaves but was not eaten by the leaf beetle, the same as the leaf beetle, Oteng-oteng (Aulacophora similis) only liked one leaf, namely preferring eggplant (Solanum melongena) leaves for 30 minutes slowly and stopped the other four leaves but the oteng-oteng didn't eat them.